Enhancing Resilience through Nuclear Emergency Preparedness at El Dabaa Site - Waad Saleh; Juyoul Kim (Science and Technology of Nuclear Installations)
The research utilized advanced PCTRAN and RASCAL software to evaluate the potential radiological impacts of hypothetical accidents, specifically loss-of-coolant accident (LOCA) and long-term station blackout (LTSBO), at the El Dabaa Nuclear Power Plant. Over a span of ten years, comprehensive meteorological data were meticulously analyzed to assess the dispersion of radioactive substances within a 40-kilometer radius across all four seasons. The outcomes revealed that only in the case of LTSBO did the radiological levels surpass the limits set by the Environmental Protection Agency (EPA). Notably, during spring, LTSBO exhibited a maximum total effective dose equivalent (TEDE) value of 13 millisieverts (mSv) at a distance of 3.2 kilometers, and the highest thyroid dose (TD) recorded was 63 mSv at 8 kilometers. These significant findings play a crucial role in shaping strategies related to the distribution of potassium iodide (KI) and further enhance the overall preparedness and evacuation planning protocols.